ANTECEDENT IN DEVELOPING VILLAGE ECONOMIC CENTER IN REMBANG DISTRICT CENTRAL JAVA INDONESIA - Hendro Sasongko; Yuary Farradia; Retno Martanti Endah Lestari; Hamzah Hamzah; Hasrul Hasrul; Herman Herman (International Journal of Engagement and Empowerment, 2023)
Local economic development is one of the Indonesia national development strategy in order to achieve sustainable development goals. Villages sustainable development goals will contribute to the local economic development. Establishing a village economic centre is one of the strategy to support village sustainable development. Rembang district located in Northern Java has potential production on various agribusiness products. A village economic centre in Rembang will play a key role for villages development. Collaboration program among village’s stakeholders such as between education institution with the village community are important namely community services. A community service in Rembang district was done to educate the community on how important to conduct feasibility study and analysis before execute various development strategy such as technology, information system and human resource development. The result of this community service was an understanding and commitment from village stakeholders that continuous village economic centre have to be established based on feasibility study